2015
DOI: 10.3109/1547691x.2015.1008656
|View full text |Cite
|
Sign up to set email alerts
|

The lymphocyte transformation test in allergic contact dermatitis: New opportunities

Abstract: Allergic contact dermatitis (ACD) is driven by the activation and proliferation of allergen-specific memory T-lymphocytes and is currently diagnosed by patch testing with a selected panel of chemical allergens. The lymphocyte transformation test (LTT) can be used to monitor ex vivo T-lymphocyte responses to antigens, including contact allergens. The LTT is not viewed as being an alternative to patch testing, but it does seek to reflect experimentally skin sensitization to specific chemicals. The LTT is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 93 publications
0
23
0
4
Order By: Relevance
“…155,156 9 | DIAGNOSING NICKEL ALLERGY Nickel allergy is diagnosed by patch testing on the upper back, as indicated by clinical suspicion of allergic contact dermatitis. 157 Other methods, which have been used mainly for research purposes, are in vitro testing, for example, the macrophage migration test, the lymphocyte blastic transformation test, and the lymphocyte transformation test, 158 the memory-lymphocyte immunostimulation assay, 159 and intradermal testing. 160…”
Section: Tolerancementioning
confidence: 99%
“…155,156 9 | DIAGNOSING NICKEL ALLERGY Nickel allergy is diagnosed by patch testing on the upper back, as indicated by clinical suspicion of allergic contact dermatitis. 157 Other methods, which have been used mainly for research purposes, are in vitro testing, for example, the macrophage migration test, the lymphocyte blastic transformation test, and the lymphocyte transformation test, 158 the memory-lymphocyte immunostimulation assay, 159 and intradermal testing. 160…”
Section: Tolerancementioning
confidence: 99%
“…With an average prevalence of ∼6% in European patients tested for contact allergy, contact sensitization in response to cobalt represents the second most prevalent metal allergy . Instead of applying suspected antigens directly on the skin in the patch test, the proliferation of lymphocytes isolated from blood in response to the suspected allergen can be assessed with the lymphocyte proliferation test (LPT), also known as the lymphocyte transformation test . In vitro testing circumvents the problem of inducing strong local reactions, and avoids the risk of active sensitization of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Instead of applying suspected antigens directly on the skin in the patch test, 3 the proliferation of lymphocytes isolated from blood in response to the suspected allergen can be assessed with the lymphocyte proliferation test (LPT), also known as the lymphocyte transformation test. 4 In vitro testing circumvents the problem of inducing strong local reactions, and avoids the risk of active sensitization of the patient. The LPT, however, is time-consuming and needs specialized laboratory staff and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Popple et al[37] and Pichler and Tilch[38] suggested that DLSTs should be undertaken following remission, that is, at about four-to-eight weeks, as the tests may generate false-negative results, because of the strong activation of regulatory T cells or the uneven distribution of memory T cells caused by ongoing hypersensitivity reactions[37,38]. Because the patient consent is not obtained, a second DLST cannot be conducted on samples from that patient.…”
Section: Discussionmentioning
confidence: 99%